1998
DOI: 10.1098/rspb.1998.0321
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites reveal heterosis in red deer

Abstract: The ¢tness consequences of inbreeding and outbreeding are poorly understood in natural populations. We explore two microsatellite-based variables, individual heterozygosity (likely to correlate with recent inbreeding) and a new individual-speci¢c internal distance measure, mean d 2 (focusing on events deeper in the pedigree), in relation to two measures of ¢tness expressed early in life, birth weight and neonatal survival, in 670 red deer calves (Cervus elaphus) born on the Isle of Rum between 1982 and 1996. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
466
9
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(499 citation statements)
references
References 38 publications
21
466
9
3
Order By: Relevance
“…The publication of the measure mean d-squared, an estimator of microsatellite allele similarity, and the demonstration that it predicts aspects of fitness in deer and seals (Coltman et al, 1998;Coulson et al, 1998) stimulated renewed interest in the link between heterozygosity and fitness (David, 1998). Subsequent studies have developed both new and more effective measures for estimating heterozygosity (Coltman et al, 1999;Amos et al, 2001;Aparicio et al, 2006) and confirmed that panels of as few as 10 presumed neutral microsatellite markers often reveal statistically significant correlations with fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The publication of the measure mean d-squared, an estimator of microsatellite allele similarity, and the demonstration that it predicts aspects of fitness in deer and seals (Coltman et al, 1998;Coulson et al, 1998) stimulated renewed interest in the link between heterozygosity and fitness (David, 1998). Subsequent studies have developed both new and more effective measures for estimating heterozygosity (Coltman et al, 1999;Amos et al, 2001;Aparicio et al, 2006) and confirmed that panels of as few as 10 presumed neutral microsatellite markers often reveal statistically significant correlations with fitness.…”
Section: Introductionmentioning
confidence: 99%
“…IR reflects the relatedness of the parents of an individual by determining the degree of allele-sharing relative to random expectations across all loci (Amos et al 2001). Standardized mean d 2 (hereafter referred to as d 2 ) is a measure focused on events deeper in the pedigree than individual heterozygosity (Hedrick et al 2001) and is based on the genetic distance between parental gamete genomes (Coulson et al 1998(Coulson et al , 1999. d 2 was calculated for each individual as the squared distance in repeat units between two alleles at a given locus, averaged over all loci typed for that individual (Coulson et al 1999) and then standardized by dividing each value by the maximum observed at that locus (Hedrick et al 2001).…”
Section: Molecular Metrics Of Heterozygositymentioning
confidence: 99%
“…Molecular metrics are commonly used as a surrogate for pedigree inbreeding coefficients (f), because the latter can be logistically difficult to obtain within natural populations. The most frequently used molecular metrics of heterozygosity in HFCs analyses include standardized multilocus heterozygosity (stMLH; Coltman et al 1999), internal relatedness (IR; Amos et al 2001) and standardized mean d 2 (Coulson et al 1998). However, it has been suggested that the correlation between molecular heterozygosity and pedigree inbreeding coefficients is too weak to be of biological significance (Coltman and Slate 2003;Balloux et al 2004;Slate et al 2004;Hansson and Westerberg 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the negative effects of inbreeding (or the positive effects of outbreeding) have been found more often among females than males. The differences in the effects of heterozygosity or inbreeding between males and females may be explained by sex-specific gene expression (Yun and Agrawal 2014), maternal investments (Charpentier et al 2006), food acquisition (Charpentier et al 2006), growth strategies (Coulson et al 1998), sexual selection pressure and life history (Ebel and Phillips 2016).…”
Section: Introductionmentioning
confidence: 99%